Filling Disks of Hayman Type of Meromorphic Functions. (31st May 2016) - Wu, Nan; Xuan, Zuxing
Abstract : We obtain the existence of the filling disks with respect to Hayman directions. We prove that, under the condition limsup r → ∞ ⁡ ( T r, f / log ⁡ r 3 ) = ∞, there exists a sequence of filling disks of Hayman type, and these filling disks can determine a Hayman direction. Every meromorphic function of positive and finite order ρ has a sequence of filling disks of Hayman type, which can also determine a Hayman direction of order ρ .